PLANT SPECIES INCLUDED IN THE “RED BOOK " OF THE REPUBLIC OF UZBEKISTAN IN THE FLORA OF THE ZAMIN AND NUROTA STATE RESERVE - Azimova Dilnoz Ergashevna, Sharipova Mohistara Xamdam qizi, Xushnazarova Nurpari Dilshodjon qizi (Journals Park Publishing, 2023)
This article provides information about plant species included in the "Red Book" of the Republic of Uzbekistan in the flora of the Zomin and Nurota State Reserves.